Modeling ICT Perceptions and Views of Urban Front Liners - Galit Cohen-Blankenstain; Peter Nijkamp; Kees van Montfort (Tinbergen Institute, 2003)
This paper offers both a conceptual and an operationalmodel that aims to map out the causes and implicationsof ICT perceptions and views of urban policy makersand/or administrative officials (denoted as urban frontliners). This is followed by the presentation of an opera-tional path model, viz. a linear structural equations model(Lisrel). The model serves to describe and test the rela-tionships between perceptions of the city, policy makers'beliefs about ICT and the associated urban ICT policy.According to the model, respondents that perceive theircity as having many urban functions (e.g., commercialcentre, service centre, higher education centre) have moreawareness to various ICT tools and are likely to consider amultiplicity of ICT measures as relevant to their city. Re-spondents that consider their city as having severe bottle-necks (e.g., traffic congestion, housing shortage) are lesslikely to think of ICT measures and ICT -related goals asrelevant to their city, nor that the municipality impactssignificantly on ICT in the city. Furthermore, respondentsthat perceive their city as suffering from many socio-economic problems (unemployment, ageing population,industrial decline and so on), are likely to consider manyICT tools as relevant to their city, although they have a lowawareness of the specific tools to be deployed. Finally,respondents who believe that ICT will affect significantly(and positively) the city and its administration, tend to at-tach a high municipal influence on ICT, and consider manyICT initiatives as relevant to their city.
Keywords: R00; 330; ICT; perceptions; Lisrel model; urban decisionmakers; Informationstechnik; Kommunalpolitik